2015
DOI: 10.1016/j.pmrj.2015.06.442
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Yoga on Balance and Fear of Falling in Older Adults

Abstract: Yoga is a potential intervention to reduce fear of falling and improve balance in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 27 publications
2
47
0
1
Order By: Relevance
“…In one study individuals were randomly assigned to yoga practice sessions or a control group that received no intervention [133]. The yoga group performed better on the fall and on the balance scale.…”
Section: Balancementioning
confidence: 99%
“…In one study individuals were randomly assigned to yoga practice sessions or a control group that received no intervention [133]. The yoga group performed better on the fall and on the balance scale.…”
Section: Balancementioning
confidence: 99%
“…The amount of information regarding program design varied greatly across these reports: some only included a list of poses [10, 11, 14]; some provided detailed information of pose progression [15, 16]; some included pose illustrations [12, 17]; others described the programs without pose details [79, 13, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…Ülger and Yağlı (2011) found the significant improvement of balance in women with musculoskeletal disorders aged 30-45 yr who practised hatha yoga 2 days a week for 4 weeks [45]. Nick et al also indicated an improvement of balance and decreasing fear of falling in people aged 60-74 yr after hatha yoga training 2 days a week for 8 weeks [32].…”
Section: Effects Of Hatha Yoga Training On the Health-related Aspectsmentioning
confidence: 98%